Assessing the Appropriateness of Repeat MRI Scan Requests Within a Foot and Ankle Department - Amir Hossain Gahanbani Ardakani BSc (Hons), MBBS; Anil Haldar MBBS BSc(Hons) FRCS PGCert; Shelain Patel FRCS(Orth); Matthew J. Welck MD. MSc. BSc; Nicholas Cullen MBBs, BSc, FRCS(TrOrth); Karan Malhotra MBChB (Hons), MRCS, FRCS (TrOrth) (Foot & Ankle Orthopaedics, 2023)
Category: Other Introduction/Purpose: With diagnostic resources often in great demand, it is important to ensure clinicians request investigations appropriately. Unnecessary radiological investigations are costly and delay patient care. This study aimed to assess the incidence and appropriateness of repeat MRI scans being requested in a single foot and ankle unit, to identify areas which can be improved. Methods: This was a retrospective analysis of 1322 scans between October-2019 to October-2022. We included all patients who had a diagnostic MRI scan requested after being assessed in our foot-and-ankle clinics. Assessments were made on the proportion of repeat scans, the seniority of requester, the indications put forward for the repeat scan, the modality of patient assessment (telephone vs face-to-face appointment), and the impact on patient management. A scan was considered a repeat, if the same anatomical location was scanned within a 3-year period. Scans were deemed appropriate if they were: part of a clinical trial, for tumour/infection/stress-fracture monitoring, for new trauma, pre-operative planning, following agreement in MDT discussions, or following significant changes in clinical symptoms. We expected that scans should ideally only be requested where the result is expected to influence management and that a scan should not be repeated without evidence of change in clinical symptoms (unless for monitoring). Results: Over the 3-year period, 6.5% of MRI scans performed were considered repeat scans. The average time between initial and repeat scans was 13.1±8.6months (range 1-33 months). 88% of patients had only one repeat scan. The majority(58%) of repeat scans were requested by non-senior clinicians. In total, 47/85(55%) scans were deemed appropriate. 75% of the patients in this cohort had been assessed face-to-face. Twenty of these scans were repeated for significant change in clinical symptoms and 50% meaningfully influenced management plans. Conversely, 38/85(45%) repeat scans did not have strong clinical indications. The majority(80%) of these were requested by non- senior clinicians and 50% were requested after a telephone review. From the scans requested by the non-senior clinicians, none(0%) had a meaningfully influence on patients’ management plans. Conclusion: This study highlights that although repeat MRI scans were not common, they seldom influenced patient management unless there was a meaningful change in patient symptoms. MRI scans were more likely to influence management when initiated by senior clinicians and following a face-to-face assessment. In order to streamline patient care and reduce unnecessary investigations we propose a protocol to guide the requesting of repeat scans. This protocol includes identifying significant symptomatic change, in-person review, and senior clinician or multi-disciplinary input when a repeat scan is being considered.